Abstracts from the 5th International Conference for Healthcare and Medical Students (ICHAMS). Issue 4 (July 2016) - Sweeney, Yvonne; O'Neill, Hugh; Duffy, Garry; Creegan, Daniel; Bustos, Viviana; Harvey, Brian; Dalphy, Alexander; O'Grady, Anthony; Kay, Elaine; Samelska, Katarzyna; Izdebska, Justyna; Kurowska, Anna; et al.
Table of contents O1: Assessing the protective effect of dexrazoxane against doxorubicin-induced toxicity in HL-1 cardiomyocytes Yvonne Sweeney, Hugh O'Neill, Garry Duffy O2: Role of KCNQ1 in epithelial barrier repair Daniel Creegan, Viviana Bustos, Brian J. Harvey O3: The suitability of non-small cell lung cancer cytology preparations for the analysis of anaplastic lymphoma kinase gene rearrangements Alexander Dalphy, Anthony O'Grady, Elaine Kay O4: Penetrating keratoplasty and descemet's stripping automated endothelial keratoplasty may lead to deterioration in glaucoma management Katarzyna Samelska, Justyna Izdebska, Anna Kurowska O5: The effect of Resolvin D1 on normal and cystic fibrosis human bronchial epithelium Rena Al-Zubaidy, Magdalena Mroz, Brian Harvey O6: Validity of clinical assessment compared with plantar fascia thickness on ultrasound for plantar fasciitis: a cross-sectional study Ryan Fagan, Helen French, Vanessa Cuddy, Jennifer Ashton, Michelle Clarke P1: Undergraduate medical research in Gulf Cooperation Council (GCC) countries: A descriptive study of students' views Zaid Sayedalamin, Mukhtiar Baig, Osama Almutairi, Hassan Allam, Taher F. Halawa, Hazem M. Atta P2: Positive fluid balance as a prognostic factor in children with sepsis during first 3 hours of resuscitation in intensive care unit Linda Sirone, Renars Erts, Jana Pavare P3: Patients on aspirin: Too little or too much? Louis Richter, Joseph Morris, Irene Oglesby, Eimear Dunne, Dermot Kenny P4: Beta catenin/TCF4 activation reduces KCNQ1 current in colonic monolayers Ibrahim Mohammed Mahdi Khayyat, Viviana Bustos Salgado, Brian J. Harvey P5: Size Matters. Abdominal aortic aneurysm: adherence to surveillance imaging guidelines Jonavan Tan, Daragh Moneley, Austin Leahy, Patricia Fitzgerald P6: Endoscopic retrograde cholangiopancreatography in the west of Ireland: Procedural outcomes and peri-procedural complications Evelyn Fennelly, Grace Harkin, John Lee P7: The effect of the extracellular redox environment on polyamine-platelet interactions Erica O'Sullivan, Brian Kirby, Sarah O'Neill P8: Functionalized gold nanoparticles: preliminary data on in vitro toxicity and comparative photothermal effect Diana Gonciar, Teodora Mocan, Cristian Matea, Lucian Mocan, Cornel Iancu P9: Imaging proteasomal inhibition after seizures in the brain: A study into cellular activity in the hippocampus of epileptic transgenic mice Chloe Doran, Sarah Hoolahan, Tobias Engel P10: Investigating the ability of the Olfactory epithelial stem cells to differentiate into glial cells by assessing cell morphology and marker expression Maha Alkhattab, Tijna Alekseeva, William Lackington, Fergal O'Brien P11: Beaumont Hospital cystic fibrosis service audit and annual report Nabeehah Moollan, Chloe Doran, Noel Gerry McElvaney, Cedric Gunaratnam P12: Quick cognitive screening: the 6-item cognitive impairment test and the temporal orientation score Lorraine Scanlon, Noeleen Brady, Suzanne Timmons P13: Granular analysis of causes of peritoneal dialysis technique failure in the first six months of therapy Richard Bresler, Zita Abreu, Stefan Trohonel, Joanne Bargman P14: Job satisfaction of surgeons working in hajj pilgrimage: a multicenter study Ahmad A. Mirza, Ahmed Badrek-Amoudi, Rakan H. Aun, Hussam A. Senan, Abdulrahim A. Mirza, Mohammed S. Binsaad, Mian U. Farooq P15: Investigation of the role of Bok using wild-type, bax-, bok-, and bax/bok-double-deficient mice Saheli Nandi, Beatrice D'Orsi, Jochen Prehn P16: Is it possible to predict resistance of an organism to stress based on the level of corticosterone? Mariia Zharova, Pavel Umrukhin P17: Investigating the strength model of self-regulation (ego depletion) and medical decision making and error in medical students Wendy Evans-Uhegbu, Frank Doyle, Hope Kudryashova, Derek Dorris, Anthony Cummins P18: Does bladder drainage with intermittent catheterisation preserve kidney function in boys with posterior urethral valves? Jemma Doheny-Shanley, Mark Woodward, Wesley Hayes P19: Investigating the role of Stonin 2, a Clathrin Mediated Endocytosis adaptor protein, in altered hippocampal synaptic transmission characterized in schizophrenia Marina Yostos, David Cotter, Melanie Focking P20: Predicting complications after colon resection Samantha Stancu, Florin Iordache, Bogdan A. Popescu P21: Knowledge, attitude and practice of the methods of primary and secondary prevention of cervical cancer among NYSC members in Lagos state, Nigeria Muhammad-Mujtaba A. Akanmu, Alero A. Robert, Ezekiel O. Oridota P22: Incidental glucose and lipid metabolisms disorders among office workers: a cross sectional study Ahmad A. Mirza, Ali K. Alzahrani, Omar Alfarhan, Essam Nour Eldin P23: Differentiating clinically significant spinal injuries; a review of emergency department presentations Bronagh MacManus, Owen Keane, Patrick Hillery, James Lee, Hugh O'Reilly, Niamh Collins P24: Pattern of renal colic occurrence due to urinary stones during Ramadan and other months of the year at King Abdulaziz Medical City, Riyadh, KSA Ibrahim Abu saq, Abdullah Al Mufarrih, Muath Jaafari, Abdullah Al Mahayni, Amen Bawazir, Sultan Alkhateeb P25: Proteomic analysis reveals novel AIB1 co-factors that may contribute to acquired endocrine resistance in breast cancer Amenah Dhannoon, Damir Vareslija, Arnold Hill, Leonie Young P26: Improving sedation practice in general ICU in Beaumont Hospital Declan Donoghue, Criona Walsh, Aileen McCabe, John Pope, Saturnino Pasco, Caroline Fallon, Don Solanki, Fiona Kiernan, Sinead Galvin, Jquan Mucvimicc, Johanna Mulvihill P27: Diagnosis and control of hypertension as indicators of the level of awareness among relatives of medical students Ahmad A. Mirza, Soha A. Elmosry P28: Evaluation of the antitumor potential from extracts of endemic plants of Brazilian caatinga against melanoma and hepatocarcinoma Lorenza Andres Ameida De Souza, Yuri de Oliveira, Diego Menezes, Alene Vanessa Santos P29: The role of Chromogranin A as a biomarker in drug resistant neuroblastoma Ahmad Zaki Asraf, Raymond Stallings, Olga Piskareva, Ross Conlon P30: Membrane sweep at term gestation in CUMH; a case-control study Siún Sweeney-Landers, Cathy Burke P31: Study of the variability of glucose levels in patients with diabetes undergoing continuous glucose monitoring Paraic Behan, Seamus Sreenan P32: Inflammatory cytokine response to decreased plasma alpha-1 antitrypsin levels in individuals with the MZ genotype Ahmed Organjee, Tatsiana Crosbie-Staunton, Emer Reeves, Noel McElvaney P33: Analysing the role of SRC-1 in breast cancer stem cell formation and activity Crystal Mieres, Leonie Young, Sara Charmsaz P34: Screening Streptococcus pneumoniae isolates for virulence genes Aya Al-Jalamdeh, Mary Corcoran, Martha McElligott, Niall Stevens, Hilary Humphreys P35: Assessment of the relevance of admission clerking criteria taught to medical students at King Abdulaziz University to real hospital practice Rashid Barnawi, Abdulaziz Ghurab, Sultan Alfaer, Hassan Balubaid, Kamal Hanbazazah, Mohammed Bukhari P36: Pattern of emergency department visits during Hajj period Mohammed Alsakkaf, Ahmad Mirza, Amrallah Mohammed P37: Anti-Dengue activity of Aspergillus terreus (sulochrin); An in vitro study Anastasia Pratanata, Maria Nathania, Tsabita Annisa, Beti Dewi P38: The comorbidome in alpha-1 antitrypsin deficiency Kuok Zhen Lee, Tomas P. Carroll, Laura Fee, Noel G. McElvaney P39: MLO-Y4 cells behave more like osteocytes in response to mechanical stimulation when cultured in 3D Rachel C. White, Robert T Brady, Fergal O'Brien